Exploring the role of nutritional status and anthropometric factors in anemia among adolescent girls in Pekanbaru, Indonesia - Fachriani Putri; Suyanto Suyanto; Ridha Restila; Agung Dwi Laksono; Tonny Sundjaya (SAGE Open Medicine)
Objective: To comprehensively analyze the factors associated with anemia among adolescent girls in Pekanbaru, with a focus on nutritional status and anthropometric factors. Methods: A cross-sectional study was conducted among 230 adolescent girls aged 10–19 years in Pekanbaru from six State Senior High Schools. Simple random sampling technique with proportional allocation to size was used to select the participants. Anemia was defined as hemoglobin levels below the WHO cut-off point. Data on age, menstrual patterns, iron supplementation, and knowledge of anemia were collected from structured interviews, dietary intake from 24-h food recall questionnaires, anthropometric measurements from height, weight, body mass index, mid-upper arm circumference. Results: The prevalence of anemia among adolescent girls in Pekanbaru was 19.9%. The average age of the adolescent girls was 15 years with a menarche age of 12 years. Although statistically insignificant through bivariate testing, it was found that negative attitudes toward iron supplementation, noncompliance in taking iron supplements, and low mid-upper arm circumference may increase the risk of anemia among respondents. Multivariate analysis showed that variables that significantly influenced anemia were low mid-upper arm circumference (PR = 1.951, 95% CI: 1.05–3.60), nutritional status underweight (PR = 0.506, 95% CI: 0.26–0.96), and vitamin B12 intake (PR = 0.558, 95% CI: 0.31–0.97). Adolescent girls with low mid-upper arm circumference had a 1.95 times higher risk of experiencing anemia after controlling for other variables. Conclusion: Anemia among adolescent girls in Pekanbaru were significantly associated with low mid-upper arm circumference (<22 cm), nutritional status (underweight), and vitamin B12 intake. A comprehensive and sustained approach is recommended, including enhanced nutrition education, and dietary diversification.